Empty : a memoir - Burton, Susan, 1973- (Random House, 2020)
"Susan Burton is ready to come clean. Happily married with two children, working at her dream job, she has lived a secret life of compulsive eating and starving for twenty-five years. This is the story not only of loosening the grip of her compulsion but of moving past her shame and learning to tell her secret."--